Hydrophobic oleophylic modified sponge, preparation method thereof and application of hydrophobic oleophylic modified sponge in oil-water separation
By forming covalent organic polymers on the surface of porous sponge, the problems of environmental pollution and poor durability in oil-water separation technology are solved, and efficient and stable oil-water separation effect is achieved, and fluorine-based pollution is avoided.
Patent Information
- Application Number
- CN202411420964.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing oil-water separation technology has problems of environmental pollution and poor durability, especially in the process of oil extraction and transportation. It is difficult for traditional methods to effectively treat oil-water emulsions and dissolved oil, which affects emission standards and product quality.
Covalent organic polymers are used to polymerize in situ on the surface of the porous sponge to form a hydrophobic and oil-friendly modified sponge, which improves oil absorption capacity and durability, and does not introduce fluorine or other contaminating elements.
It significantly improves the hydrophobicity, acid and alkali resistance stability and oil absorption properties of the sponge, and achieves efficient separation of oil and water separation, and is environmentally friendly.
Smart Images

Figure CN119240857A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil-water separation, and in particular to a hydrophobic and lipophilic modified sponge, a preparation method thereof, and application thereof in oil-water separation. Background Art
[0002] With the rapid development of industry, the discharge of oily wastewater is increasing, and the frequent oil spills during oil extraction and transportation will have an extremely serious impact on the ecological environment. In addition, the oil-water mixture does not only include clearly stratified oil-water mixtures, but sometimes there will be oil-water emulsions and a small amount of oil dissolved in water. For example, in the rare earth extraction and separation process, the hydrophilicity of the organic phase increases after saponification, and the entrainment of the extractant and diluent and the incomplete phase separation will cause the rare earth raffinate and stripping liquid to often contain oil pollutants, affecting the subsequent emission standards and the quality of rare earth products.
[0003] The Chinese invention patent with publication number CN116619504A provides a method for preparing a super-hydrophobic modified wood sponge for long-term separation of oil and water, by treating the surface of the wood sponge with a fluorosilane / pyrrole solution and a ferric chloride solution in sequence, so as to grow a super-hydrophobic polypyrrole nanomaterial on the surface of the wood sponge. However, the addition of fluorine-containing substances will have a great impact on the environment. The Chinese invention patent with publication number CN113332965A provides a magnetic fly ash @ PDMS sponge material for oil-water separation, which can only adsorb cyclohexane six times its own weight during oil-water separation, and its oil-water separation performance is difficult to sustain and its durability is poor. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a hydrophobic and lipophilic modified sponge and a preparation method and application in oil-water separation. The present invention utilizes a covalent organic polymer with acid and alkali resistance, stability and low density to grow on the surface of a porous sponge, thereby obtaining a modified sponge material with hydrophobic and lipophilic properties, without the need to introduce fluorine and other polluting elements, and at the same time can greatly improve the oil absorption capacity of the porous sponge itself as well as the durability and property stability during oil-water separation.
[0005] In the first aspect, the present invention provides a hydrophobic and lipophilic modified sponge, comprising a porous sponge and a covalent organic polymer in situ polymerized on the skeleton surface of the porous sponge, and the loading amount of the covalent organic polymer on the modified sponge is 10-15%; wherein the covalent organic polymer comprises trimesaldehyde and 4,4'-diaminodiphenylmethane copolymerized.
[0006] The hydrophobic and oleophilic modified sponge provided by the present invention can reduce the surface hydrophilicity by in-situ polymerization to form a covalent organic polymer (COF) on the surface of the porous sponge. At the same time, after the COF is in-situ polymerized on the surface of the porous sponge, the bonding strength between the two can be improved. At the same time, the surface of the COF is a rough structure at a microscopic level, which can increase the contact angle between the material surface and water, thereby improving the hydrophobicity. In addition, COF also has good acid and alkali resistance stability and low density characteristics, which can improve the property stability and durability of the modified sponge during use.
[0007] Optionally, the porous sponge includes at least one of melamine sponge, polyurethane sponge, cellulose sponge and silicone sponge.
[0008] In a second aspect, the present invention also provides a method for preparing a hydrophobic and lipophilic modified sponge, comprising: modifying a porous sponge by infiltrating it into a copolymer solution, and then separating and drying it to obtain a modified sponge; the solute in the copolymer solution comprises trimesaldehyde and 4,4'-diaminodiphenylmethane.
[0009] Optionally, when the porous sponge is infiltrated and modified in the copolymerization solution, the trimesaldehyde and the 4,4'-diaminodiphenylmethane are grown by in-situ polymerization on the surface of the porous sponge under the catalysis of a catalyst.
[0010] Optionally, the porous sponge includes at least one of melamine sponge, polyurethane sponge, cellulose sponge and silicone sponge.
[0011] Optionally, the molar ratio of the trimesaldehyde to the 4,4'-diaminodiphenylmethane is 1:(1-2).
[0012] Optionally, the catalyst includes at least one of acetic acid, formic acid, and benzenesulfonic acid.
[0013] Optionally, the molar concentration of the catalyst in the copolymerization solution is 3-6 mol / L.
[0014] Optionally, the solvent in the copolymerization solution includes at least one of 1,4-dioxane and mesitylene.
[0015] Optionally, the trimesaldehyde and the 4,4'-diaminodiphenylmethane are grown by in-situ polymerization on the surface of the porous sponge at 110-130° C. and under the catalysis of a catalyst.
[0016] Optionally, after separation, washing and drying in a vacuum environment at 50-70° C., a modified sponge is obtained.
[0017] Optionally, before the porous sponge is infiltrated and modified in the copolymerization solution, the porous sponge is infiltrated and cleaned with an ethanol solution and deionized water and then dried.
[0018] In a third aspect, the present invention also provides an application of a hydrophobic and lipophilic modified sponge in oil-water separation.
[0019] Optionally, the hydrophobic-lipophilic modified sponge is immersed in the oil-water mixture to be separated for adsorption separation.
[0020] Optionally, the oil-water mixture to be separated includes one of a mixture of an organic solvent and water, a mixture of oil and water, a rare earth raffinate, and a rare earth stripping solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the modified sponge prepared in Example 1 of the present invention;
[0022] Figure 2 FT-IR spectrum of the modified sponge prepared in Example 1 of the present invention;
[0023] Figure 3 This is a state change diagram of the modified sponge prepared in Example 1 of the present invention when performing oil-water separation of a mixture of an organic solvent and water;
[0024] Figure 4 The modified sponge prepared in Example 1 of the present invention is used for oil droplet changes before and after oil-water separation of kerosene-in-water emulsion;
[0025] Figure 5 The modified sponge prepared in Example 1 of the present invention is used for oil droplet changes before and after oil-water separation of kerosene-in-water emulsion;
[0026] Figure 6 The modified sponge prepared in Example 1 of the present invention is used for mixed organic phases with saponification degrees of 0%, 30%, and 50% (P 507 -kerosene) and water emulsion before and after separation of oil droplets;
[0027] Figure 7 This is a characterization diagram of the surface hydrophobicity of the modified sponge prepared in Example 1 of the present invention.
[0028] Figure 8 This is a characterization diagram of the surface hydrophobicity of the modified sponge prepared in Example 1 of the present invention after being treated in acid, alkali and salt environments for 3 days. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0030] The present invention provides a hydrophobic and lipophilic modified sponge, comprising a porous sponge and a covalent organic polymer in situ polymerized on the surface of the skeleton of the porous sponge. In fact, the porous sponge has high porosity and hydrophilic and lipophilic properties. However, after the covalent organic polymer is polymerized on the surface of the skeleton of the porous sponge, the roughness of the surface of the skeleton of the porous sponge can be greatly improved, thereby improving the hydrophobicity and retaining the lipophilicity.
[0031] In fact, the loading amount of the modified sponge on the porous sponge is 10-15%, so that it can be evenly dispersed on the skeleton surface of the porous sponge, which is beneficial to improve the hydrophobicity of the porous sponge.
[0032] Specifically, the covalent organic polymer includes trimesic acid aldehyde and 4,4'-diaminodiphenylmethane copolymerized. In fact, by copolymerizing trimesic acid aldehyde and 4,4'-diaminodiphenylmethane on the skeleton surface of the porous sponge, the active groups existing in the porous sponge itself can be effectively utilized for in-situ polymerization, thereby effectively improving the bonding strength of the covalent organic polymer on the porous sponge and avoiding the covalent organic polymer from falling off during the compression process of the modified sponge.
[0033] In some embodiments, the porous sponge in the modified sponge as the elastic matrix can be selected from at least one of melamine sponge, polyurethane sponge, cellulose sponge and silicone sponge. In fact, the porous sponge is selected from a sponge material with hydrophilic and lipophilic properties. In addition, the porous sponge can be selected from a conventional commercial product to achieve the purpose of facilitating the selection of raw materials and reducing the reaction cost.
[0034] The present invention also provides a method for preparing a hydrophobic and lipophilic modified sponge, comprising: infiltrating a porous sponge into a copolymerization solution for modification, and then separating and drying to obtain a modified sponge. In fact, by infiltrating the porous sponge into the copolymerization solution, the porous sponge can absorb the copolymerization solution into the interior due to its water absorption, which is conducive to the uniform formation of the covalent organic polymer in the copolymerization solution on the skeleton surface of the porous sponge.
[0035] In fact, the solutes in the copolymerization solution include trimesaldehyde and 4,4'-diaminodiphenylmethane. When the porous sponge is immersed in the copolymerization solution, trimesaldehyde and 4,4'-diaminodiphenylmethane undergo a condensation reaction on the surface of the porous sponge, and the aldehyde group in trimesaldehyde condenses with the amino group in 4,4'-diaminodiphenylmethane to form an imine bond, thereby forming a stable covalent organic polymer on the skeleton surface of the porous sponge.
[0036] In some embodiments, when the porous sponge is immersed in the copolymerization solution, trimesaldehyde and 4,4'-diaminodiphenylmethane are polymerized and grown in situ on the surface of the porous sponge under the catalytic action of the catalyst. In fact, the addition of the catalyst can effectively promote the generation of the copolymerization reaction, thereby promoting the formation of the covalent organic polymer on the surface of the porous sponge. Specifically, the catalyst can be selected from at least one of acetic acid, formic acid, and benzenesulfonic acid.
[0037] In some embodiments, the molar ratio of trimesaldehyde to 4,4'-diaminodiphenylmethane in the copolymerization solution is 1:(1-2), and 4,4'-diaminodiphenylmethane is actually set in excess, which is conducive to the in-situ copolymerization of the covalent organic polymer on the surface of the porous sponge. In addition, the molar concentration of the catalyst in the copolymerization solution is 3-6 mol / L, which is conducive to catalyzing the copolymerization reaction, and the solvent in the copolymerization solution includes at least one of 1,4-dioxane and mesitylene.
[0038] In some embodiments, the porous solution is immersed in the copolymerization solution, and trimesic acid and 4,4'-diaminodiphenylmethane are in situ polymerized and grown on the surface of the porous sponge at 110-130°C under the catalysis of the catalyst. In fact, the reaction at 110-130°C is conducive to the formation of covalent organic polymers and reduces the generation of by-products.
[0039] In some embodiments, before the porous sponge is infiltrated and modified in the copolymer solution, the porous sponge is pre-infiltrated and cleaned with an ethanol solution and deionized water and dried, which is beneficial to improve the cleanliness of the porous sponge and the number of active sites on the surface of the porous sponge skeleton. In addition, after the porous sponge is infiltrated and modified, it is separated and cyclically cleaned with N,N-dimethylformamide and acetone, and then dried in a vacuum environment at 50-70°C to obtain a modified sponge.
[0040] The present invention also provides an application of any of the above modified sponges in oil-water separation, wherein the modified sponge is immersed in the oil-water mixture to be separated and in contact with the oil phase, and the oil phase in the mixture is adsorbed, so that the oil phase components and the water phase components are separated from each other. Specifically, the oil-water mixture to be separated includes a mixture of an organic solvent and water, a mixture of oil and water, a rare earth raffinate, and a rare earth stripping solution.
[0041] Example 1
[0042] This embodiment 1 provides a method for preparing a hydrophobic and lipophilic modified sponge, comprising the following steps:
[0043] S1. Wet a melamine sponge with a size of 1 cm×1 cm×1 cm in an ethanol solution and ultrasonically clean it. After three cycles, take out the melamine sponge, rinse it with deionized water three times, and then transfer it to a 60° C. oven and dry it to constant weight;
[0044] S2, 32.4 mg (0.2 mmol) of 1,3,5-benzenetricarboxaldehyde (TFB) and 39.6 mg (0.2 mmol) of 4,4'-diaminodiphenylmethane (MDA) were added into 15 mL of 1,4-dioxane and then ultrasonically mixed and dissolved to obtain a copolymer solution;
[0045] S3. Immerse the cleaned and dried melamine sponge in the copolymerization solution and mix ultrasonically for 10 minutes. Then add 2 mL of acetic acid as a catalyst and react at 120°C for 24 hours. Then take out the sponge and wash it three times with N,N-dimethylformamide and acetone. Then, transfer it to a 60°C vacuum drying oven and dry it for 12 hours until the weight is constant to obtain a hydrophobic and lipophilic modified sponge (TFB-MDA@MS). The loading amount of the covalent organic polymer formed by the copolymerization of 1,3,5-benzenetricarboxaldehyde and 4,4'-diaminodiphenylmethane on the modified sponge is calculated to be 13.33%.
[0046] Performance Testing
[0047] The TFB-MDA@MS prepared in Example 1 was characterized by SEM. Figure 1 As shown, chemical bond analysis was performed by FT-IR spectroscopy, and its FT-IR spectrum is shown in Figure 2 As shown. Figure 2 It can be seen that in both MS and TFB-MDA@MS, the -1 The broad stretching vibration peak is due to the stretching vibration of secondary amine (NH), and TFB-MDA@MS and TFB-MDA have different peaks at 1620 cm -1 A vibration stretching peak belonging to C=N produced by Schiff base reaction appeared at , which indicates the successful polymerization of TFB-MDA on melamine sponge.
[0048] Test Example 1
[0049] The modified sponge (TFB-MDA@MS) prepared in Example 1 is subjected to oil-water separation of a mixture of an organic solvent and water, comprising the following steps:
[0050] J1. After adding 5 mL of chloroform to Sudan III for dyeing, the mixture was mixed with 100 mL of deionized water, and the chloroform settled to the bottom of the mixture, thereby obtaining an oil-water mixture to be separated;
[0051] J2. The modified sponge is placed deep into the oil-water mixture to be separated. When the modified sponge is in the water phase, a silver mirror phenomenon is formed on the surface. After the modified sponge contacts chloroform, the chloroform is quickly absorbed.
[0052] J3. After the modified sponge that absorbs chloroform is taken out from the liquid surface, chloroform does not drip, so that clean deionized water without chloroform is obtained, and the oil-water separation of the organic solvent and water mixture is realized.
[0053] In fact, when oil-water separation is performed in Test Example 1, Figure 3 As shown, from Figure 3 It can be clearly seen that when the modified sponge comes into contact with chloroform, it can quickly absorb the chloroform, so that the red chloroform quickly spreads into the modified sponge, and no dripping occurs after adsorption.
[0054] Test Example 2
[0055] The modified sponge (TFB-MDA@MS) prepared in Example 1 was subjected to an adsorption performance stability test, including: subjecting the modified sponge to saturated adsorption-extrusion cycle adsorption tests on chloroform and kerosene, respectively, and calculating the saturated adsorption amount of the modified sponge at the 1st, 5th, 10th, 15th, 20th, 25th, 30th, and 35th times, and calculating the retention rate of the saturated adsorption at the 5th, 10th, 15th, 20th, 25th, 30th, and 35th times compared with the 1st time, and the results are shown in Table 1 below.
[0056] Table 1 Adsorption performance stability test of modified sponge
[0057]
[0058] It can be seen from Table 1 that the modified sponge prepared by the present invention has good performance stability during the adsorption and extrusion desorption of oil phase components, and the COF structure on the surface of the modified sponge has good elasticity and stability.
[0059] Test Example 3
[0060] The modified sponge (TFB-MDA@MS) prepared in Example 1 is used to separate oil from water of kerosene-in-water emulsion, comprising the following steps:
[0061] J1. Mix kerosene and deionized water at a volume ratio of 1:10 by ultrasonic mixing for 1 h to obtain a milky white kerosene-in-water emulsion;
[0062] J2. Immerse the modified sponge in a kerosene-in-water emulsion and shake it to obtain a transparent aqueous solution after adsorption and separation.
[0063] This shows that the modified sponge prepared in Example 1 has a good separation effect on the kerosene-in-water emulsion, and the changes in the emulsion before separation and the transparent aqueous solution after separation are observed by optical microscopy. Figure 4 As shown, from Figure 4 In the figure, it can be seen that there are obvious organic phase droplets in the emulsion at a size of 100 μm, while no organic phase droplets can be observed at the same scale after separation. At the same time, after measuring the kerosene content before and after separation using an ultraviolet spectrophotometer, it was calculated that the separation efficiency of the modified sponge for kerosene is 98.35%.
[0064] Test Example 4
[0065] The modified sponge (TFB-MDA@MS) prepared in Example 1 is used to separate oil and water from a kerosene-in-water emulsion, comprising the following steps:
[0066] J1. Mix kerosene and deionized water at a volume ratio of 10:1 by ultrasonic mixing for 1 h to obtain a milky white kerosene-in-water emulsion;
[0067] J2. Immerse the modified sponge in kerosene-water emulsion and shake it to obtain a transparent aqueous solution after adsorption and separation.
[0068] This shows that the modified sponge prepared in Example 1 has a good separation effect on the kerosene-in-water emulsion, and the changes in the emulsion before separation and the transparent aqueous solution after separation are observed by optical microscope. Figure 5 As shown, from Figure 5 In the figure, it can be seen that there are obvious organic phase droplets in the emulsion at a size of 100 μm, but no organic phase droplets can be observed at the same scale after separation. At the same time, after measuring the kerosene content before and after separation using an ultraviolet spectrophotometer, it was calculated that the separation efficiency of the modified sponge for kerosene is 99.08%.
[0069] Test Example 5
[0070] The modified sponge (TFB-MDA@MS) prepared in Example 1 was used for mixed organic phases (P 507 - kerosene) and water emulsion, comprising the following steps:
[0071] J1, P 507 The mixture was mixed with kerosene at a volume ratio of 1:1 to obtain a mixed solution with a saponification degree of 0%, and the mixed solution was ultrasonically mixed with water at a volume ratio of 1:10 for 1 hour to obtain an emulsion with a saponification degree of 0%;
[0072] J2. A sodium hydroxide solution with a concentration of 0.01 mol / L was added dropwise into the mixed solution with a saponification degree of 0%, and the mixture was kept at a constant temperature of 25°C for 30 min, and then the mixture was allowed to stand for stratification to obtain an organic phase with a saponification degree of 30%. The organic phase was then ultrasonically treated with water at a volume ratio of 1:10 for 1 h to obtain an emulsion with a saponification degree of 30%;
[0073] J3. A sodium hydroxide solution with a concentration of 0.01 mol / L was added dropwise into the mixed solution with a saponification degree of 0%, and the mixture was kept at a constant temperature of 25°C for 30 min, and then the mixture was allowed to stand for stratification to obtain an organic phase with a saponification degree of 50%. The organic phase was then ultrasonically treated with water at a volume ratio of 1:10 for 1 h to obtain an emulsion with a saponification degree of 50%;
[0074] J4. The modified sponge was immersed in an emulsion with a saponification degree of 0%, an emulsion with a saponification degree of 30%, and an emulsion with a saponification degree of 50%, respectively, and a transparent aqueous solution was obtained after oscillating adsorption and separation.
[0075] Before separation, the oil droplets in the emulsions with a saponification degree of 0%, 30%, and 50% were observed under an optical microscope at a scale of 100 μm. Figure 6 As shown in (a1), (b1), and (c1) in FIG. 1 , the oil droplets in the emulsion are observed under an optical microscope at the same scale after separation. Figure 4 As shown in (a2), (b2) and (c2) in the figure.
[0076] from Figure 6 It can be seen that it is difficult to observe oil droplets in the aqueous solution after separation, and the separation efficiencies of 0%, 30% and 50% emulsions with saponification degrees were measured by UV spectrophotometer to be 92.02%, 88.55% and 84.05%, respectively.
[0077] Test Example 6
[0078] The modified sponge (TFB-MDA@MS) prepared in Example 1 was tested for acid resistance, alkali resistance and salt resistance, including the following steps: pre-measuring the water contact angle of the modified sponge in the initial state as follows: Figure 7 As shown; the modified sponge was immersed in a hydrochloric acid solution with a pH of 1, a sodium hydroxide solution with a pH of 13, and a 5wt.% sodium chloride aqueous solution for three days, and then the modified sponge was taken out and washed with ethanol and dried. The changes in the water contact angle of the modified sponge after immersion in an acidic environment, an alkaline environment, and a saline environment were measured, as shown in FIG. Figure 8 shown.
[0079] from Figure 7 and Figure 8It can be seen that the water contact angle of the modified sponge prepared in Example 1 is 147.7° in the initial state, which indicates that the modified sponge has good hydrophobicity, and after being immersed in acidic, alkaline and salt solutions, the water contact angle is stably maintained above 140°, which indicates that the modified sponge can maintain chemical stability in a complex acid-base environment and has good acid resistance, alkali resistance and salt resistance.
[0080] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A hydrophobic and lipophilic modified sponge, characterized in that: The invention comprises a porous sponge and a covalent organic polymer in situ polymerized on the skeleton surface of the porous sponge, wherein the loading amount of the covalent organic polymer on the modified sponge is 10-15%; wherein the covalent organic polymer is formed by copolymerization of trimesaldehyde and 4,4'-diaminodiphenylmethane.
2. The hydrophobic and oleophilic modified sponge according to claim 1, characterized in that: The porous sponge includes at least one of melamine sponge, polyurethane sponge, cellulose sponge and silicone sponge.
3. A method for preparing a hydrophobic and lipophilic modified sponge, characterized in that: include: The porous sponge is impregnated and modified in a copolymerization solution, and then separated and dried to obtain a modified sponge; The solute in the copolymerization solution includes trimesaldehyde and 4,4'-diaminodiphenylmethane.
4. The preparation method according to claim 3, characterized in that: When the porous sponge is infiltrated and modified in the copolymerization solution, the trimesaldehyde and the 4,4'-diaminodiphenylmethane are grown by in-situ polymerization on the surface of the porous sponge under the catalysis of the catalyst.
5. The preparation method according to claim 4, characterized in that: The porous sponge includes at least one of melamine sponge, polyurethane sponge, cellulose sponge, and silica sponge; and / or the molar ratio of the trimesaldehyde to the 4,4'-diaminodiphenylmethane is 1:(1-2); and / or the catalyst includes at least one of acetic acid, formic acid, and benzenesulfonic acid; and / or the molar concentration of the catalyst in the copolymerization solution is 3-6 mol / L; and / or the solvent in the copolymerization solution includes at least one of 1,4-dioxane and mesitylene.
6. The preparation method according to claim 4, characterized in that: At 110-130° C. and under the catalysis of a catalyst, the trimesaldehyde and the 4,4′-diaminodiphenylmethane are polymerized and grown in situ on the surface of the porous sponge.
7. The preparation method according to claim 3, characterized in that: After separation, the modified sponge is washed and dried in a vacuum environment at 50-70°C.
8. The preparation method according to claim 3, characterized in that: Before the porous sponge is infiltrated and modified in the copolymerization solution, the porous sponge is infiltrated and cleaned with an ethanol solution and deionized water and then dried.
9. Use of the hydrophobic-oleophilic modified sponge according to any one of claims 1 to 2 or the hydrophobic-oleophilic modified sponge prepared by the preparation method according to any one of claims 3 to 8 in oil-water separation.
10. The use according to claim 9, characterized in that: The hydrophobic and lipophilic modified sponge is immersed in the oil-water mixture to be separated for adsorption separation; the oil-water mixture to be separated includes one of a mixture of organic solvent and water, a mixture of grease and water, a rare earth raffinate, and a rare earth stripping solution.
Citation Information
Patent Citations
Preparation method of hydrophobic oil-absorbing sponge loaded with COF-F
CN110339597A
Triphenylamino type covalent organic framework composite membrane as well as preparation method and application thereof
CN117771975A
Switchable wettability sponge and preparation method and application thereof
CN118179458A
Long alkyl chain super-hydrophobic covalent organic polymer, preparation method thereof and application of long alkyl chain super-hydrophobic covalent organic polymer in oil-water separation
CN119591842A
Covalent organic framework material as well as preparation method and application thereof
CN120230265A